Biocultural approaches to transgender and gender diverse experience and health: Integrating biomarkers and advancing gender/sex research. Issue 1 (19th December 2020) - DuBois, L. Zachary; Gibb, James K.; Juster, Robert‐Paul; Powers, Sally I.
Abstract: Transgender and gender diverse (TGD) people are increasingly visible in U.S. communities and in national media. With this increased visibility, access to gender affirming healthcare is also on the rise, particularly for urban youth. Political backlash and entrenchment in a gender binary, however, continue to marginalize TGD people, increasing risk for health disparities. The 2016 National Institute of Health recognition of sexual and gender minority people as a health disparities population increases available funding for much‐needed research. In this article, we speak to the need for a biocultural human biology of gender/sex diversity by delineating factors that influence physiological functioning, mental health, and physical health of TGD people. We propose that many of these factors can best be investigated with minimally invasively collected biomarker samples (MICBS) and discuss how to integrate MICBS into research inclusive of TGD people. Research use of MICBS among TGD people remains limited, and wider use could enable essential biological and health data to be collected from a population often excluded from research. We provide a broad overview of terminology and current literature, point to key research questions, and address potential challenges researchers might face when aiming to integrate MCIBS in research inclusive of transgender and gender diverse people. We argue that, when used effectively, MICBS can enhance human biologists' ability to empirically measure physiology and health‐related outcomes and enable more accurate identification of pathways linking human experience, embodiment, and health.